Peran Kesbangpol Nusa Tenggara Barat Dalam Meresolusi Konflik Jemaah Ahmadiyah Guna Mewujudkan Keamanan Nasional - Relycia Solihin; Herlina Juni Risma Saragih; Bayu Setiawan; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Ahmadiyya is a sect that was opposed by the MUI through a Fatwa in 2005 and the goverment with SKB No. 3 of 2008 with the hope that the Ahmadiyya Congregation and the opponents understand each other and resolve the chaos. But in reality, between 1998 and 2018, violence still occurred. This study aims to describe the role of the NTB National Unity and Politics Agency (Kesbangpol) in resolving the Ahmadiyya Congregation conflict to achieve national security. This study uses a qualitative research methodology. The subject and object of research are the Province of NTB, conflict, and conflict resolution carried out by the NTB Kesbangpol through direct interviews and documentation. The results of this study indicate that the NTB Kesbangpol made various role, namely: (1) Before the conflicts, focused on meeting with Belief Monitoring Team, Religious Leaders, Community Leaders and Ahmadiyya Congregation to detect and discuss conflicts and also establish forums to coordinate and SKB socialization. (2) During the conflicts, focused on stopping violence in collaboration with the police and localizing the Ahmadiyya congregation to a safer place. (3) Post-conflict, focused on preparing facilities, infrastructure, fullfiling human rights, and forming an Early Alertness Program to minimize similar conflicts from reoccurring. The role played by the NTB Kesbangpol has shown negative peace and positive peace. However, the Ahmadiyya Congregation conflict has not been fully resolved, so the Kesbangpol of NTB must establish a Working Group for the Acceleration of Conflict Management and engage in massive community education about the SKB.